USE OF COLLECTED BARLEY IN HOME CONDITIONS - I. R. Askarov; D. T. Khasanova; D. T. Khasanova (Web of Journals Publishing, 2024)
The article presents the importance of using enriched food products in functional nutrition. Here, the beneficial aspects of harvested barley have been highlighted. Information is also provided on the preparation and use of barley malt at home. Some recommendations for using milled barley at home are given.
Keywords: barley malt, home conditions, amino acids and polyphenol compounds, enzymes, mineral substances, hormones, lysine, methionine, tryptophan, histidine, arginine.